VO离合词的离析现象 ： 基于普通话与新加坡华语对比研究 = A corpus-based comparative study of VO separable verbs in Mainland Mandarin and Singapore Mandarin Chinese - 符传婧 Foo, Chuan Jing (2014)
关于VO“离合词”应归类为词语或词组的问题，尽管语言学界探讨甚多，但一直存在不同意见。有别于前人研究，本文从普通话和新加坡华语着眼，比较研究(a)普通话语料库中VO离合词的离析现象及与前人研究的异同；(b)普通话语料库与新加坡华语语料库中VO离合词的使用分布及其词汇化进程异同(Brinton and Traugott 2005)。本文的普通话和新加坡华语语料分别取自北京大学CCL语料库和东南亚华文媒体语料库。在前人研究（如Her (1996)，王海峰（2010）等）基础上，本文查看使用频率较高的离合词在两个汉语变体中的多方面句法表现（如体标记“了、着、过”在VO离合词中的出现位置等），从而比较其所表现的词或词组特征。本研究发现普通话离合词与前人研究在归类上有所异同，而且普通话与新加坡华语中的离合词使用也有所差异。本文的语料库调查发现普通话和华语中不同的离合词表现不同的词与词组特点，因此不同于前人“词vs. 词组”简单两分法或较为笼统的“词vs.词组vs.中间状态”三分法，本文认为VO离合词分布在“词----双种状态----词组 ”连续统上的不同位置，有些更接近词组，有些更接近词。本研究利用大型语料库揭示常用VO离合词在两个汉语变体中不同的词汇化进程，本研究的结果可为将来深入探讨VO离合词提供参考。Regarding on whether VO “Separable Words” should be classified as words or phrases, despite of many discussions by different linguists, all linguists still have differing opinions. Unlike previous studies, this paper focuses on Mainland Mandarin (PUTONGHUA) and Singapore Mandarin Chinese (XINJIAPO HUAYU), and exhibits a comparative study on (a) Mainland Mandarin (PUTONGHUA) Corpus with previous studies, on the separation phenomenon of VO Separable Verbs; (b) Mainland Mandarin (PUTONGHUA) Corpus with Singapore Mandarin Chinese Corpus, on the distribution of VO Separable Verbs and the process of lexicalization (Brinton and Traugott 2005). Through corpus analysis, this paper discovers that Separable Verbs present different word and phrase characteristics in Mainland Mandarin and Singapore Chinese. Unlike previous studies whereby Separable Verbs are either simply seen as a “word vs. phrase” dichotomy or a “word vs. phrase vs. intermediate state” trichotomy, this paper argues that VO Separable Verbs are distributed at different positions on the continuum of “word--dual status-- phrase”, with some closer to the positions of phrase while some to word. The results of this paper may be used as reference for further research on VO Separable Verbs.